Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45850
|View full text |Cite
|
Sign up to set email alerts
|

Stall Warning by Blade Pressure Signature Analysis

Abstract: At low mass flow rates axial compressors suffer from flow instabilities leading to stall and surge. The inception process of these instabilities has been widely researched in the past — primarily with the aim of predicting or averting stall onset. In recent times, attention has shifted to conditions well before stall and has focussed on the level of irregularity in the blade passing signature in the rotor tip region. In general, this irregularity increases in intensity as the flow rate through the compressor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…The vortex filaments of the tip leakage vortex, which have no radial component at the exit of the tip gap, deform to produce a series of islands of positive and negative radial vorticity which convect across the passage. Low pressure regions associated with these structures were measured by Young et al [21] on the casing of the large tip gap portion of their axial compressor with eccentric clearance. Figure 15 shows simulated casing static pressure traces as the E 3 rotor with tip clearance is brought into stall.…”
Section: Full Annulus With Tip Clearancementioning
confidence: 92%
See 1 more Smart Citation
“…The vortex filaments of the tip leakage vortex, which have no radial component at the exit of the tip gap, deform to produce a series of islands of positive and negative radial vorticity which convect across the passage. Low pressure regions associated with these structures were measured by Young et al [21] on the casing of the large tip gap portion of their axial compressor with eccentric clearance. Figure 15 shows simulated casing static pressure traces as the E 3 rotor with tip clearance is brought into stall.…”
Section: Full Annulus With Tip Clearancementioning
confidence: 92%
“…To provide experimental verification of the structures and mechanisms discerned from the E 3 computations, a series of tests were performed on a low speed single stage compressor at the University of Cambridge. Details of the machine are given by Young et al [21] and are summarised in Table 2.…”
Section: Cambridge Low Speed Compressormentioning
confidence: 99%
“…In order to capture the transient unsteady flow phenomena at the spike stall inception, a new measurement technique of the casing pressure was applied. This measurement can obtain instantaneous casing pressure fields inside one blade passage; this differs from the technique presented by Young et al [10] in that several pressure transducers are positioned in one blade pitch. Details of the technique are presented below in subsequent section.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…The high-frequency waves, which are observed as rotating low-pressure disturbances, are considered to result from multiple short length-scale part-span stall cells, and the flow structure of the stall cell consists of a tornado-like separation vortex spanning from the blade suction surface to the casing wall ahead of the rotor [8,9]. Recently, Young et al confirmed that low-pressure regions already form in the forward part of the blade passage before stall occurs, and they propagate as prestall disturbances [10]. Based on a numerical study on stall inception in centrifugal compressor vaned diffusers, Everitt et al suggested that the development of vortical structures near the end wall, which are generated by shedding of vorticity from the leading edge, may be common to the spike stall in axial compressors [11].…”
Section: Introductionmentioning
confidence: 99%
“…After analysing the data from both low-speed and high-speed compressors, they defined the correlation measure dropped below a given threshold as an "event" and found time between events decreases as flow rate close to the stall boundary. Young et al [14] did some further investigation of the correlation measure on a low-speed compressor and found the value of the correlation measure was strongly affected by both tip-clearance size and eccentricity.…”
Section: Introductionmentioning
confidence: 99%